Experimental characterization of turbulent boundary layers around a NACA 4412 wing profile - Mallor, Fermin; Sanmiguel Vila, Carlos; Hajipour, Majid; Vinuesa, Ricardo; Schlatter, Philipp; Örlü, Ramis (Experimental Thermal and Fluid Science, 2025)
An experimental characterization of the turbulent boundary layers developing around a NACA 4412 wing profile is carried out in the Minimum Turbulence Level (MTL) wind tunnel located at KTH Royal Institute of Technology. The campaign included collecting wall-pressure data via built-in pressure taps, capturing velocity signals in the turbulent boundary layers (TBLs) using hot-wire anemometry (HWA), and conducting direct skin-friction measurements with oil-film interferometry (OFI). The research spanned two chord-based Reynolds numbers (Rec=4×105 and 106) and four angles of attack (5°, 8°, 11° and 14°), encompassing a broad spectrum of flow conditions, from mild to strong adverse-pressure gradients (APGs), including scenarios where the TBL detaches from the wing surface. This dataset offers crucial insights into TBL behavior under varied flow conditions, particularly in the context of APGs. Key features include the quasi-independence of the pressure coefficient distributions from Reynolds number, which aids in distinguishing Reynolds-number effects from those due to APG strengths. The study also reveals changes in TBL dynamics as separation approaches, with energy shifting from the inner to the outer region and the eventual transition to a free-shear flow state post-separation. Additionally, the diagnostic scaling in the outer region under spatial-resolution effects is considered, showing further evidence for its applicability for small L+, however with inconsistent results for larger L+. The findings and database resulting from this campaign may be of special relevance for the development and validation of turbulence models, especially in the context of aeronautical applications.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Adverse-pressure gradient; Hot-wire anemometry; Turbulence scaling; Turbulent boundary layer; Wind-tunnel experiment